The influence of team culture on team performance: the mediating role of team commitment and team work engagement - Castro, Ana Rita Antunes de (2021)
This study inquiries into the direct influence of team culture on team performance and the mediating role of both team commitment and team work engagement on their relationship. Through a questionnaire, we collected a sample of 86 participants who were employed in teams and statistically analysed the data. Methods included data analysis in IBM SPSS Statistics 27, Hayes's PROCESS Macro 3.1 (2018). Results corroborate the existence of a positive relationship between team culture and team commitment, team work engagement and team performance. The results also show a mediating effect of team commitment and team work engagement between team culture and team performance. This study can be a launch point for further research on the importance of team cultures within an organisation.